Review on Drug Regulatory Science Promoting COVID-19 Vaccine Development in China - Zhiming Huang; Zhihao Fu; Junzhi Wang (Engineering, 2022)
Regulatory science is a discipline that uses comprehensive methods of natural science, social science, and humanities to provide support for administrative decision-making through the development of new tools, standards, and approaches to assess the safety, efficacy, quality, and performance of regulated products. During the pandemics induced by infectious diseases, such as H1N1 flu, severe acute respiratory syndrome (SARS), and Middle East respiratory syndrome (MERS), regulatory science strongly supported the development of drugs and vaccines to respond to the viruses. In particular, with the support of research on drug regulatory science, vaccines have played a major role in the prevention and control of coronavirus disease 2019 (COVID-19). This review summarizes the overall state of the vaccine industry, research and development (R&D) of COVID-19 vaccines in China, and the general state of regulatory science and supervision for vaccines in China. Further, this review highlights how regulatory science has promoted the R&D of Chinese COVID-19 vaccines, with analyses from the aspects of national-level planning, relevant laws and regulations, technical guidelines, quality control platforms, and post-marketing supervision. Ultimately, this review provides a reference for the formulation of a vaccine development strategy in response to the current pandemic and the field of vaccine development in the post-pandemic era, as well as guidance on how to better respond to emerging and recurring infectious diseases that may occur in the future.